The Influence of Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) on Firm Value in the Coal Mining Subsector Listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 Period. - Haslinda Haslinda; Nurman Nurman; Rezky Amalia Hamka; Anwar Ramli; Muh Ichwan Musa (Journal of Innovative and Creativity, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) on firm value, proxied by Price to Book Value (PBV), in coal mining subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period, both partially and simultaneously. The research employed a quantitative approach using panel data regression analysis. The sample consisted of 12 coal mining subsector companies selected through purposive sampling. Secondary data were obtained from annual financial statements published by the Indonesia Stock Exchange and analyzed using Eviews The selection of the regression model was conducted through Chow test, Hausman test, and Lagrange Multiplier test, resulting in the Random Effect Model (REM) as the best-fit model. The results indicate that ROA, DER, and CR have a positive but insignificant effect on firm value (PBV) partially. Simultaneously, the three variables also show a positive but insignificant effect on firm value. These findings suggest that the fundamental factors of the companies are not yet able to explain variations in firm value in the coal mining subsector during the study period, considering the high dynamics of commodity prices and other external factors that influence market perceptions.